Edukasi Perilaku Seksual, Gender, dan HIV/AIDS pada Siswa SMA Negeri 6 Padang dan Masyarakat - Dien Gusta Anggraini Nursal; Degina Rahmadhanti; Indah Yovi Permata Putri; Lis Natahdiya Laulaa; Shylvi Yunitri Darman; Rani Basmir (Warta Pengabdian Andalas, 2023)
Behaviour faced by adolescents such as dating, free sex, pornography, bullying, physical and sexual violence, abortion, HIV/AIDS and sexually transmitted diseases to malnutrition, obesity and anaemia. The problems can result in teenagers experiencing psychological problems, slow growth and inappropriate nutrition. Conversely, in pre-elderly and older people with low knowledge about current nutrition, Menopause can interfere with productivity in daily activities. This counselling purpose was to increase adolescents' knowledge regarding behavioural education on sexual activity, namely preventing HIV/AIDS and reproductive tract infections, preventing unwanted pregnancy, preventing sexual violence to the limit pornography, and increasing the knowledge of older people regarding nutrition fulfilled at Menopause. The implementation method was by lecturing with the assistance power point and question and answer to the target. Collecting data used a pre-test and post-test questionnaire; the amount of each material was ten questions. Based on statistical tests and results in the frequency distribution, there was an increase in question scores; Wilxocon test results increased the knowledge of pre-test and post-test participants of counselling with the effectiveness of counselling using the gain score test that is low - moderate. These results showed an influence of counselling activities on sexual behaviour education in adolescents and reproductive age.